Regulation of Insurance Mediation in Conditions of Euro Integration Processes of Ukraine - Шолойко, Антоніна Сергіївна (Київський національний університет імені Тараса Шевченка, 2016)
Здійснено огляд вітчизняного та європейського законодавства у сфері регулювання страхового посередництва. Визначено суб'єктів і об'єкт регулювання страхового посередництва. Охарактеризовано порядок нормативно-правового наближення в умовах зміни законодавства Європейського союзу щодо регулювання страхового посередництва. Представлено порівняння положень законодавства щодо регулювання страхового посередництва в Україні та ЄС. Надано пропозиції щодо адаптації вітчизняного законодавства до європейського у сфері регулювання страхового посередництва в умовах євроінтеграційних процесів.

The review of national and European legislation in the field of regulation of insurance mediation is made. Subjects and object of regulation of insurance mediation are defined. The order of the legislative approximation in conditions of changing legislation of regulation of insurance mediation in European Union is characterized. A comparison of legal provisions to regulate insurance mediation in Ukraine and the EU is done. Suggestions of adaptation national legislation to the European in the area of regulation of insurance mediation in conditions of euro integration processes are represented. The main are the next: – it is advisable to expand the object and the scope of regulation of insurance mediation and set appropriate limits to the subjects for which the sale of insurance products is not the main activity; – it is necessary to introduce a regular improvement of the knowledge and skills for insurance distributors because of the development of insurance conditions and changing of economic environment; – it is necessary to create the order of compulsory professional indemnity insurance in accordance with the requirements of the Directive on insurance distribution; – before the signing of the contract it is necessary to disclosure to customers of insurance products the information about the status of insurance distributors and type of remuneration that they receive; – if the insurance product is in addition to the goods or services, insurance distributor shall inform the client about the possibility of buying various product components separately with the presentation of their characteristics.
Регулювання страхового посередництва в умовах євроінтеграційних процесів України
Keywords: страхове посередництво; страхові посередники; страхові дистриб'ютори; регулювання страхового посередництва; insurance mediation; insurance intermediaries; insurance distributors; regulation of insurance mediation